Silverstream eco‐hydraulics flume: Hydraulic design and tests - V. I. Nikora; D. G. Goring; B. J. F. Biggs (New Zealand Journal of Marine and Freshwater Research, 1998)
Hydraulic design details are presented of the Silverstream eco‐hydraulics flume, which is a 12 m long by 75 cm wide tilting outdoor flume situated on the left bank of the Silverstream River, 30 km north of Christchurch, New Zealand. Results of testing, both mechanical and hydraulic, are presented and discussed. The mechanical adjustments required to accommodate the weight of water in the flume and thermal expansion and contraction of the frame (exacerbated by being outside) are described. Hydraulic calibration experiments using Acoustic Doppler Velocimetry indicate that there is a central portion at least 4 m long by 15–20 cm wide of the flume where the flow is uniform and 2‐dimensional. Regions up stream and down stream of this area are affected by entrance and exit conditions. Close to the side walls, cells of helical secondary currents were found, and these appear to be separated from the zone of 2‐dimensional flow by narrow regions with anomalous turbulence properties. The “frozen” turbulence hypothesis was proven true by the calibration experiments. These findings can have implications in eco‐hydraulic experiments on organism‐flow interactions, mass transfer, and uptake processes.